Hubungan Indeks Massa Tubuh (IMT) Dengan Keseimbangan Postural dan Fleksibilitas - Iqbal Fajar Nugroho; Reshandi Nugraha; Asep Sumpena (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the relationship between Body Mass Index (BMI) and postural balance and correlation in students aged 11–13 years at SMP Negeri 26 Bandung. The study used a correlational design with a quantitative approach and stratified random sampling technique, with a sample size of 72 students. BMI was measured based on weight and height, postural balance was measured using a composite score, and turning using the V-sit and Reach tests. The Shapiro-Wilk normality test showed that the BMI data were not normally distributed, so the correlation analysis used the Spearman Rank test, while the Pearson test was used for the underweight category. The results showed no significant relationship between BMI and postural balance (ρ = 0.035; p > 0.05) or initial (ρ = -0.100; p > 0.05), including in the underweight, ideal, and overweight BMI categories. It was concluded that BMI had no significant relationship with students' postural balance and cycling, suggesting that motor skills were more influenced by other factors such as physical activity, neuromuscular coordination, and movement experience. Keywords: Body Mass Index, Flexibility, Postural Balance